ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH DENGAN DUKUNGAN PIMPINAN SEBAGAI VARIABEL MODERATING PADA ORGANISASI PERANGKAT DAERAH PEMERINTAH PROVINSI SUMATERA UTARA - Zili Saidah; Eka Nurmala Sari; Prawidya Hariani (Fakultas Ekonomi Universitas Negeri Medan, 2023)
The purpose of this study is to determine and analyze whether the use of technology has an effect on of SIMDA implementation effectiveness. To find out and analyze whether competency has an effect on SIMDA implementation effectiveness. To find out and analyze whether the clarity of motivation has an effect on SIMDA implementation effectiveness. To find out and analyze whether Leader Support moderates has an impact of the use of technology has an effect on SIMDA implementation effectiveness. To find out and analyze whether Leader Support moderates the effect of competence on of SIMDA implementation effectiveness. To find out and analyze whether Leader Support moderates the effect of motivation on SIMDA implementation effectiveness. The research approach uses quantitative associative. This research uses data analysis method using SmartPLS.3 software which is run with computer media. In this study, the research instrument used was a questionnaire. The variable measurement scale used in this study is to use an ordinal scale in the form of a Likert scale. The sample of this study is the population of 30 OPD in the North Sumatra Provincial Government with 3 respondents in this study, each OPD of 90 people who function in accounting/finance, and employees who work as head of the accounting/finance section of staff.. Based on the results of the research, the use of technology, competence, motivation, has a significant positive effect on effectiveness of SIMDA implementation. Leader Support as moderating variable can moderate the effect of the use of technology, competence, motivation, on effectiveness of SIMDA implementation with Regional Organizaton of North Sumatera Government. Keywords: The Use of Technology, Competency, Motivation, Effectiveness of SIMDA Implementation, Leader Support